MODEL PROBLEM BASED LEARNING (PBL) DISERTAI TUGAS DALAM PEMBELAJARAN FISIKA DI SMA - Masyhuri Masyhuri; Albertus Djoko Lesmono; Rif'ati Dina Handayani (FKIP Universitas Jember, 2017)
The purpose of this study are: (1) Assessing the influence model of ProblemBased Learning (PBL) with the task to learning outcomes of students with learningcommonly used in schools; (2) Assessing the influence model of Problem BasedLearning (PBL) with the task of the science process skills of students in physics inhigh school. This type of research is an experimental research. Research wasconducted in the second semester of the 2015/2016 academic year. The populationin this study were all students of class X SMAN 1 Jenggawah. Where the researchwas determined by purposive sampling method area.Techniques and data collectioninstruments used in this study are: observation using observation sheet, in the formof portfolio assessment results Student Worksheet (LKS), tests using the deviceachievement test (post-test), interviews, and documentation.Based on data analysisand discussion, the conclusion of this research are : There is a difference in studentlearning and science process skills high school science class X students betweenclasses eksperimens the control classKeywords: multirepresentation, student worksheet, Problem Based Learningmodel.